Secret Key Steganography with Message Obfuscation by Pseudo-random Number Generators - Gutiérrez Cárdenas, Juan M. (2014)
Steganography is the art of concealing information within different types of media objects such as images or audio files. Its counterpart, Steganalysis, is the study of methods that uncover information in a suspicious file, which has being altered for stego purposes. Its techniques rely on the inspection of changes at the pixel information level. In this paper, we propose a method for Secret-key Steganography that uses a picture to conceal a message with unaltered pixel information, so it would be secure against Steganalysis inspection techniques. This is possible using a technique derived from code obfuscation using random numbers. In summary, we will modify the stego-key transmitted during the communication process, which maps the information in the unaltered cover image. So the original message will be reconstructed by the receiver using the seeds of Pseudo-Random Number Generators, included in the stego-key. The proposed technique is secure against classical steganalysis attacks because it leaves the original and generated stego images unchanged.